Boron-containing coating yields enhanced antimicrobial and mechanical effects on translucent zirconia - Sabino, Clarice Ferreira [UNESP]; Agarwalla, Shruti Vidhawan; da Silva Rodrigues, Camila [UNESP]; da Silva, Ana Carolina [UNESP]; Campos, Tiago Moreira Bastos; Tan, Kai Soo; Rosa, Vinicius; de Melo, Renata Marques [UNESP] (Elsevier, 2024)
Objectives: To evaluate the mechanical and antimicrobial properties of boron-containing coating on translucent zirconia (5Y-PSZ). Methods: 5Y-PSZ discs (Control) were coated with a glaze (Glaze), silver- (AgCoat), or boron-containing (BCoat) glasses. The coatings' antimicrobial potential was characterized using S. mutans biofilms after 48 h via viable colony-forming units (CFU), metabolic activity (CV) assays, and quantification of extracellular polysaccharide matrix (EPS). Biofilm architectures were imaged under scanning electron and confocal laser scanning microscopies (SEM and CLSM). The cytocompatibility was determined at 24 h via WST-1 and LIVE&DEAD assays using periodontal ligament stem cells (PDLSCs). The coatings' effects on properties were characterized by Vickers hardness, biaxial bending tests, and fractography analysis. Statistical analyses were performed via one-way ANOVA, Tukey's tests, Weibull analysis, and Pearson's correlation analysis. Results: BCoat significantly decreased biofilm formation, having the lowest CFU and metabolic activity compared with the other groups. BCoat and AgCoat presented the lowest EPS, followed by Glaze and Control. SEM and CLSM images revealed that the biofilms on BCoat were thin and sparse, with lower biovolume. In contrast, the other groups yielded robust biofilms with higher biovolume. The cytocompatibility was similar in all groups. BCoat, AgCoat, and Glaze also presented similar hardness and were significantly lower than Control. BCoat had the highest flexural strength, characteristic strength and Weibull parameters (σF: 625 MPa; σ0: 620 MPa; m = 11.5), followed by AgCoat (σF: 464 MPa; σ0: 478 MPa; m = 5.3). Significance: BCoat is a cytocompatible coating with promising antimicrobial properties that can improve the mechanical properties and reliability of 5Y-PSZ.
Keywords: Ceramic; Fracture strength; Glass; Mechanical properties; S. mutans biofilm; Surface modification